Self-education of the teacher as a condition of personal and professional development - Голозубова, О. В.; Матенко, Є. П. (Scientific notes of the pedagogical department, 2018)
The goal of the Ukrainian education system is to create conditions for the development and self-realisation of each individual, the formation of generations that are able to learn during lifetime. This approach takes on special significance in the formation of the personality of the future teacher, who will subsequently influence on the formation of the personality of his/her students. Teacher self-education is one of the ways to achieve this goal. In the article self-education is considered as a necessary condition for the personal and professional self-development of the teacher, its importance for the pedagogical profession is defined. It is noted that the peculiarity of the pedagogical understanding of self-education consists in considering it as a process requiring special pedagogical support; a process that does not occur spontaneously, in a natural way, but only as a result of a specially organized pedagogical influence. The structure of a teacher’s self-education (self-assessment, self-determination, self-organization, self-realization, self-criticism, self-control, self-development) is defined. Specific functions of self-education are revealed, such as: the function of forming the perfect personality of the teacher; function of developing the ability to choose; function to improve the level of the teacher’s qualification; function of development of specific psychological qualities of the teacher. The author identifies the main directions of the process of self-education. The main is the direction of self-education, stemming from the main professional and pedagogical tasks. The direction of self-education is important for teachers, due to the modern features of the pedagogical profession. primary, basic secondary and full secondary education are characterized. The role of self-education in enhancing the professionalism of a modern teacher is revealed. Forms of self-educational activity of teachers of primary, basic secondary and full secondary education are characterized.